2001
DOI: 10.1021/jp003586k
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Adsorption on the (110)-Oriented Diamond Surface

Abstract: Multiple internal reflection infrared spectroscopy (MIRIRS) and temperature-programmed desorption (TPD) were used to investigate the interaction of oxygen with a diamond (110)-oriented surface. Exposure of the hydrogen-free diamond surface at 90 K to room-temperature O 2 or thermally excited oxygen, O 2 * (produced with a heated iridium filament) resulted in a sharp infrared absorption at 657 cm -1 , which disappeared on heating to 300 K. The 657 cm -1 absorption may indicate a surface peroxide. When the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…Finally, these conditions were repeated with a Ni(110) sample; no O 2 desorption was observed in TPD measurements and no Ir was observed in the Auger spectra. Other studies using Ir filaments to generate AO have also reported no appreciable Ir accumulation from a hot Ir filament [45]. These control experiments verify that the TPD and AES uptakes observed are the result of the interaction of AO with Ag(111).…”
Section: Resultssupporting
confidence: 76%
“…Finally, these conditions were repeated with a Ni(110) sample; no O 2 desorption was observed in TPD measurements and no Ir was observed in the Auger spectra. Other studies using Ir filaments to generate AO have also reported no appreciable Ir accumulation from a hot Ir filament [45]. These control experiments verify that the TPD and AES uptakes observed are the result of the interaction of AO with Ag(111).…”
Section: Resultssupporting
confidence: 76%
“…This phenomenon has also been observed by Chalamala 1 on Mo tip arrays and indicates that at room-temperature O 2 molecules were unable to form a stable adsorbed species on the UNCD surface. The observation is in agreement with that of Mackey et al, 18 and will be discussed next.…”
Section: Resultssupporting
confidence: 92%
“…4͑b͒. The desorbed species were not clear at this stage, but possible in the form of O 2 or CO/CO 2 as observed by Mackey et al 18 Figures 4͑a͒ and 4͑b͒ represent two extreme cases: Recoverable and permanent damage to the UNCD coated tip emitters operated at a relatively low and high current due to O 2 exposure.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations